Poradenstvo v podpore profesijného rozvoja pedagogických zborov škôl - Ivan Pavlov (Karolinum Press, 2019)
Both the system and the framework of support of professional development of the teaching profession have faced many changes within the school system development. It included various aims, contents, forms and methods, which were subjected to the pedeutologic research and to the teaching profession creation. The interdisciplinary approach used in the teaching profession research is currently based also on andragogy (professional), which has been offering new inputs mainly in questions related to professional learning, education and career guidance provided to employed adults. Current article details principles of a proposed model of andragogic career guidance provided to individuals and pedagogical corps at schools, which reflects current absence of complex programmes supporting professional development of the teaching profession at schools. The model of andragogic guidance has been anchored in the individualised support, but framed within pedagogical corps at schools, their needs and conditions. Vital is an about-face from external, formal support not taking into account any specific needs of pedagogical corps towards individualised guidance in the context of life and work of pedagogical corps at a school.